PELATIHAN PENGELOLAAN E-COMMERCE PADA YAYASAN PONDOK PESANTREN AL-HIKMAH MANGUNREJA KABUPATEN TASIKMALAYA - Sulidar Fitri; Muhammad Taufiq; Hani Rubiani; R Apip Miptahudin (Universitas Majalengka, 2020)
Society must be able to follow the rhythm of the times when the era of modernization is developed rapidly, especially in terms of information technology so that people must have sufficient knowledge and insight to co-exist with the era of the all-electronic as status quo. In this case, e-commerce becomes one of the easiest alternatives to support someone in entrepreneurship. Through the E-Commerce Management Training at the Al-hikmah Mangunreja boarding school foundation in Tasikmalaya Regency, which has been organized by the Muhammadiyah University of Tasikmalaya, it can provide knowledge and skills for the people sheltered by the Al-Hikmah Foundation, specifically the use of e-commerce to be able to compete in global business. The training participants from the Al-Hikmah Foundation were very enthusiastic in participating in these activities and had high expectations of participants so that service activities such as e-commerce training could be carried out on an ongoing basis and by providing diverse material in an effort to improve the ability of the community towards a prosperous society. The highest percentage obtained by 90% from the evaluation results of participants who agreed stated that the training is useful to add insight into e-commerce. Another 90% is found in statements that agree that social media as a business promotion is easy. Statements with the lowest percentage occur at half of the number of participants, 50% which states that Creating a promotional blog with wordpress is easy. Based on these figures, it shows that from several practicums that have been done, it shows that the difficulty level of the participants is more in the matter of making a wordpress blog account as a medium for business promotion.